CHALLENGES OF ACCESS TO MARKETS AND OPPORTUNITIES FOR SMALL, MEDIUM AND MICRO ENTERPRISES (SMMEs) IN BOTSWANA - Mutoko, Wilbert R. (European Scientific Journal, ESJ, 2014)
Small, Medium and Micro Enterprises (SMMEs) are the backbone of most economies of the world. SMMEs provide a means for economically empowering the economy of every nation. However, Botswana SMMEs contribute only 35% to GDP. Gross Domestic Product (GDP) is the value of a country’s overall output of goods and services at market prices excluding net income from abroad (Business Dictionary, 2014). GDP demonstrates well doing of a country in terms of productivity. In the past decade there has been an on-going debate on SMME development and SMMEs’ contribution to Botswana. The debate has involved SMMEs significance towards employment creation, poverty eradication, and economic diversification. However, SMMEs face tremendous challenges that threaten their survival and growth. The challenges include lack of or limited access to markets, financial inadequacies, limited management skills, poor work ethics and lack of competitiveness. This study explores how SMMEs are negatively affected by lack of markets. Since the advent of the world financial crisis in 2008, Botswana SMMEs have struggled to market their products because their major market was the government. Unfortunately the government due to constrained resources has frozen some projects to reduce spending. Hence, most SMMEs in Botswana went out of business. In this study, the researcher reviews what other countries have done to deal with the same challenge of lack of markets. It is hoped that the findings from experiences of Ghana, and Brazil and from literature within Botswana will help SMMEs in Botswana to successfully diversify their market and survive in business.